Postmenopausal endometriosis: current evidence and clinical challenges in diagnosis and treatment - Amber Trujillo Lalla; Jaden R Kohn; Dave Pasternak; Xiaoming Guan (Current Opinion in Obstetrics & Gynecology, 2026)
Purpose of review Endometriosis was once thought to affect only reproductive-aged women. However, 2–5% of postmenopausal individuals remain affected. Guidance for this group is limited. This review outlines an updated approach to postmenopausal endometriosis, addressing pathophysiology, diagnostic challenges, and management in both natural and surgical menopause. Recent findings Postmenopausal endometriosis is underrecognized and has many diagnostic challenges. MRI is the preferred imaging modality for detecting lesions and assessing malignancy risk, while surgery with excision remains the diagnostic and treatment gold standard. Medical treatment options are limited, with aromatase inhibitors showing the most promise by targeting main sources of estrogen production; however, research is limited. Hormonal replacement therapy is recommended after surgical or premature menopause (